Management of Fish Pond Water Waste with Aquaponics Technology at Paguyuban Budiarta 7, Bululawang District, Malang Regency: Pengelolaan Limbah Air Kolam Ikan dengan Teknologi Aquaponik di Paguyuban Budiarta 7 Kecamatan Bululawang Kabupaten Malang - Rahayu, Yekti Sri; Mufida, Muslimatul; Sunyoto (Jurnal Soeropati, 2023)
This service aims to provide solutions in the form of applying aquaponic technology to handle fish pond water waste. Aquaponic technology has the advantage of filtering wastewater to be channeled into vegetable growing media. The implementation method applied is training and assistance in aquaponic installation in the fish ponds of members of Paguyuban Budiarta 7. Aquaponic installation is in the form of installing pipes and water pumps from the fish pond to the vegetable growing media through filter and nutrient reservoirs. The results achieved are the installation of aquaponic systems in fish ponds can reduce the inundation of fish pond water waste, because the pond water is not directly discharged in the fish farming area, but channeled to the vegetable planting media, after being filtered in a water tank filled with charcoal. The results of observations of partner members show that around 90% of association members stated that this community service program provides benefits to increase knowledge and skills in diversifying fish and vegetable products through the aquaponics system. The sustainability of the program is highly expected to train members' expertise in producing energy sources through the use of solar cells, so that the use of electricity to support aquaponic installations can be more efficient and economical.